2004
DOI: 10.1007/s00204-004-0541-8
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 70 in the rat nasal cavity: localisation and response to hyperthermia

Abstract: Heat shock proteins (HSPs) are a group of proteins that are rapidly induced in response to physiological stress, including hyperthermia and exposure to toxicants. Thus they may provide a useful index of toxicity in in vitro systems for screening for toxicity. We have recently developed a rat nasal explant system for investigating upper respiratory tract toxicity, and the aims of this study were to localise HSP70 within the rat nasal cavity and to characterise its response to hyperthermia. Constitutively, HSP70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
(57 reference statements)
2
12
0
Order By: Relevance
“…In the present study as well as in all studies examining the expression of stress-induced HSPs in the OE (Kilgour et al, 2000;Carr et al, 2001Carr et al, , 2004Simpson et al, 2004Simpson et al, , 2005, the predominant cell type exhibiting HSP upregulation was the sustentacular cell. This observation is surprising given our hypothesis of a P2R role in HSP induction, as P2Rs are present on both ORNs and sustentacular cells.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In the present study as well as in all studies examining the expression of stress-induced HSPs in the OE (Kilgour et al, 2000;Carr et al, 2001Carr et al, , 2004Simpson et al, 2004Simpson et al, , 2005, the predominant cell type exhibiting HSP upregulation was the sustentacular cell. This observation is surprising given our hypothesis of a P2R role in HSP induction, as P2Rs are present on both ORNs and sustentacular cells.…”
Section: Discussionmentioning
confidence: 76%
“…In support of our hypothesis for a purinergic role in HSP25 induction, we observed that strong odorant stimulated a 3-fold increase in ATP release from OE slices in vitro. Moreover, heat shock and toxic chemicals caused a reduction in intracellular ATP levels in a rat nasal explant culture system that was concurrent with an increase in HSP70 (Simpson et al, 2004(Simpson et al, , 2005.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, in the rat olfactory system, stress-induced HSP70 production occurs primarily in supporting (sustentacular) cells and not in olfactory sensory neurons (39). In addition, olfactory sensory neurons are protected by HSP induction (40). Targeted overexpression of HSP70 in astrocytes protects CA1 hippocampal neurons from death caused by transient forebrain ischemia (41).…”
Section: Figurementioning
confidence: 99%
“…The 2-and 6-h timepoints were selected based on literature indicating that HSP expression peaks 2-6 h after heat shock (Yoshida et al 1999;Simpson et al 2004). Utricles were homogenized, and total RNA was collected (RNAEasy, Qiagen).…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%
“…In pilot experiments, we examined the effects of various temperatures and durations of heat shock, based on protocols found in the literature (Poe and O'Neill 1997;Braiden et al 2000;Ju and Tseng 2004;Simpson et al 2004). We found that exposure to temperatures above 44-C for periods as short as 10 min resulted in a significant loss of hair cells (data not shown).…”
Section: Development Of the Heat Shock Protocolmentioning
confidence: 99%